The Kriyākramakarī’s Integrative Approach to Mathematical Knowledge - Wagner, Roy (History of Science in South Asia)

(untitled) (University of Alberta Library, 2018)
The purpose of this paper is to review the general organization of knowledge in the Kriyākramakarī, a sixteenth-century treatise of Kerala mathematics. Specifically, I will argue that the authors' interest in justification or proof is integrative, rather than hierarchical or cumulative. In other words, the purpose of proofs in the Kriyākramakarī is to connect various different aspects of mathematics, rather than just establish results by means of previously known results.